ANALISIS HISTORIS KATEGORISASI UṢŪL FIQH DAN IMPLIKASINYA - Muhammad Hasan (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
The methodology of Islamic law is a very determining factor in Istinbâth (Islamic law deduction). However, the systematic methodology of Islamic law had not been invented yet in the early period of Islamic law development. In that period every mujtahid thought based on his own way of thinking to formulate Islamic law. This deliberate thought engendered various schools of thought of uṣūl al-fiqh. This writing is aimed at describing the schools of thought of uṣūl al-fiqh. The Islamic scholars categorize them into two board categories: the uṣūl al-fiqh of Shāfi’iyah and the uṣūl al-fiqh of Hanāfiyah. The uṣūl al-fiqh of Shāfi’iyah is named “the methodology of kalam scholar” and is a model for scholar of shāfi’iah, Mālikiyah, Shiah Imamiyah, Zaidiyah and also for kalam scholar of Mu’tazilah and Ash’ariah. The uṣūl al-fiqh of Hanāfiyah is identical to fiqh development. Viewed from source aspect, the writer of this school of thought depends greatly on fatwās and istinbāṭ of its predecessors. Viewed from arrangement aspect, the uṣūl of this school of thought arrangement is always followed by fiqh discussion. Such a dichotomy is worth questioning in tajdīd of uṣūl al-fiqh.